EFEKTIVITAS MODEL PEMBELAJARAN MEANS ENDS ANALYSIS (MEA) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Susanti, Erma (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The low mathematical problem-solving ability of students at SDN 008 Tembilahan Hulu, caused by teacher-centered learning and minimal method variation, is the main background of this study. To address this problem, this study focuses on testing the effectiveness of the Means Ends Analysis (MEA) learning model as an innovation to improve problem-solving skills. This study applies a quasi-experimental method with a non-equivalent control group design involving 50 third-grade students, divided into 25 students in the experimental group using the MEA model and 25 students in the control group using conventional methods. Data were collected through mathematical problem-solving tests given before (pre-test) and after (post-test) the treatment, then analyzed statistically using the t-test and N-Gain score. The main findings show that the experimental group obtained a significantly higher average post-test score (89.2) than the control group (63.2), with a t-value of 13.137 (p<0.05). The N-Gain Score analysis further confirmed that the MEA model proved to be